مؤلّفات يوسف بن حسن بن عبد الهادي ومساهمته في حفظ التّراث الفكريّ : Muʾallafāt Yūsuf b. Ḥasan b. ʿAbd al-Hādī wa-Musāhamatuhu fī Ḥifẓ al-Turāth al-Fikrī - Aljoumani, Said (Middle East and Islamic Studies E-Books Online, Collection 2021, ISBN: 9789004441286., 2021)
On the basis of a newly discovered manuscript this book offers the most comprehensive bibliography of the enormous output of the fifteenth-century scholar Ibn ʿAbd al-Hādī - enlarging our view of his scholarly contribution and correcting numerous mistakes in this regard. This book is thus essential reading for all those interested in the writerly world of Damascus and the scholarly world of the late fifteenth century, especially with regard to the Ḥanbalī tradition and ḥadīth scholarship. In particular, linking the titles of his books with the extant manuscripts in libraries around the world opens new perspectives to these scholarly worlds. At the same time this book offers a new framework to studying social history with reference to documents and the material culture of the book. في اكتشاف جديد لمخطوطة تسمية كتب يوسف بن حسن بن عبد الهادي، يُقدِّم سعيد الجوماني وكونراد هيرشلر أضبط قائمة ببليوغرافية بمؤلفاته الشخصيَّة وبخط يده؛ فنبَّهت هذه القائمة إلى جزءٍ من إنتاجه الفكري كان مجهولاً تماماً، وصححت الكثير من أخطاء القراءة في القوائم السابقة. ونشرها سيدعم الأبحاث العاملة بحقل حركة التأليف بدمشق والحياة الفكريّة فيها نهاية القرن التاسع الهجريّ، خاصّةً ما يتعلق بالتراث الحنبليّ وعلم الحديث. وسيفتح الربط بين المؤلفات المذكورة في تسمية الكتب من جهة ووقف كتب ابن عبد الهادي من جهة ثانية والمخطوطات الموجودة في مكتبات العالم من جهة ثالثة باباً جديداً إلى دراسة التراث الفكري في مدينة دمشق أواخر العهد المملوكي. وتقترح هذه الدراسة إطاراً جديداً لدراسة التاريخ الاجتماعي اعتماداً على الوثائق الشخصيَّة والهيئات الماديّة للمخطوطات الشخصيّة.